How do young people engage with climate change? The role of knowledge, values, message framing, and trusted communicators. (24th August 2015) - Corner, Adam; Roberts, Olga; Chiari, Sybille; Völler, Sonja; Mayrhuber, Elisabeth S.; Mandl, Sylvia; Monson, Kate
Abstract : Despite several decades of research on more effectively communicating climate change to the general public, there is only a limited amount of knowledge about how young people engage with an issue that will shape and define their generation. We provide a thorough review of international studies in this area, drawing on survey data and qualitative research. The review is organized into two main sections. The first briefly situates young people's engagement with climate change relative to other concerns and examines levels of awareness, concern and 'scepticism' among this age group. The second focuses on four key determinants of effective climate change communication and assess whether young people differ in any appreciable way from research findings relating to the general population. The four factors are the role of values and worldviews in determining climate change views; the efficacy of 'information‐based' interventions; the 'psychological distance' of climate change and message framing; and the role of trusted messengers. In the concluding section we discuss the implications for engaging young people more effectively and explore possibilities for future research. WIREs Clim Change 2015, 6:523–534. doi: 10.1002/wcc.353 This article is categorized under: Perceptions, Behavior, and Communication of Climate Change > Behavior Change and Responses